Electrical and thermal models of CNT TSV and graphite interface - Vaisband, Boris (2019)
Carbon nanotubes (CNTs) are a suitable replacement for metals commonly used as a fill material for through substrate vias (TSVs). The electrical and thermal contact resistance, however, between the CNT TSVs and the horizontal metal interconnects (typically copper) can limit the use of CNT technology. A replacement for the horizontal metal interconnects in the form of graphite material is proposed in this paper. Electrical and thermal models of the interface between CNT TSVs and graphite interconnect are compared to the interface between CNT TSVs and copper interconnect. The proposed models include electrical and thermal crowding effects as well as the skin effect. The CNT/graphite interface exhibits up to 72.6% and 71.9%, respectively, lower electrical and thermal resistance as compared to the CNT/copper interface.